Prehospital care providers' decision to transport the patient with a suicide attempt refusing care in the Cape Town Metropole, Western Cape: A survey based on the Mental Healthcare Act of 2002 - Evans, Katya (Division of Emergency Medicine, 2016)
Includes bibliographical references